Metodologia de priorização de ferramentas Lean Maintenance utilizando o método AHP - Silva, Luciano Barbosa da (2024)
The search for reducing production costs has driven the development of new technologies in companies, such as predictive maintenance, Industry 4.0, Big Data and Artificial Intelligence, with the aim of improving processes, especially in the maintenance sector. However, a high number of unwanted stops in processes are still observed due to the low quality of maintenance interventions, often caused by the lack of skills of professionals and the difficulty in making assertive decisions. In this way, this study addresses the problem of the lack of specific methods for making decisions based on customers needs. Decision-making in the maintenance sector is particularly challenging due to the complexity and diversity of factors to be considered. The correct choice of maintenance actions is vital to avoid unplanned outages but is hampered by the need to balance several criteria and the lack of structured decision methods. As a solution, this study proposes the use of the multi-criteria Analytical Hierarchy Process (AHP) method combined with the Lean philosophy to identify solutions for improving maintenance activities. Based on the literature review and the application of value stream mapping (VSM) on the <factory floor= during preventive shutdowns, 20 alternatives were selected, evaluated by 36 company professionals, considered maintenance customers. These professionals were divided into five hierarchical levels: operators, maintenance specialists, analysts, supervisors and managers, thus forming a multidisciplinary team. Each hierarchical level received a degree of importance on the Saaty scale, according to its decision-making level in the company. As a result, it was possible to identify the five most relevant alternatives to solve the problem in question. The proposed method proved to be relevant for the maintenance sector. The empirical approach demonstrated that the use of Lean Maintenance, combined with the AHP multi-criteria method, is capable of identifying and prioritizing maintenance activities, making the sector more effective. Therefore, with a qualitative approach based on the Voice of the Customer (VOC), it was possible to direct the maintenance department's efforts to increase the reliability and availability of equipment, reducing production costs. This study shows that the integration of structured methodologies and continuous improvement philosophies can overcome the difficulties inherent in decision-making in maintenance, providing more efficient and strategic management of maintenance activities.